FATHER'S INVOLVEMENT IN PARENTING CHILDREN WITH CEREBRAL PALSY - Siron, Yubaedi; Ningrum, Hana Sausan; Gustiani, Lingga; Muaz, Fauziah (Journal of Early Childhood Education (JECE), 2020)
Cerebral palsy children need special treatment from their parents. The optimal caring from father has a significant influence on the development of children with cerebral palsy. This study aims to explore the role of fathers in caring for children with cerebral palsy. This research uses a qualitative approach. This study uses semi-structured interviews with fathers who have children with cerebral palsy. The results of this study found that fathers play an active role in childcare. Fathers help build good relationships with children by inviting them to play, sing, and read a child's favourite storybook. Even though he is busy at work, the father always tries to fulfil the children's needs such as bathing, eating, giving medication, changing diapers and routine therapy. Each participant in this study had their parenting challenges. Although sometimes the participants feel unwilling to do therapy on children, what makes them enthusiastic is their high expectations.